The Effectiveness of the Kahoot app! on the Game Based Learning Method for Mastering the Vocabulary of SMAN 9 Pekanbaru Students - Yashinta Qhorayma Putri Akbar; Merri Silvia Basri; Dini Budiani (JETISH: Journal of Education Technology Information Social Sciences and Health, 2023)
This study aims to determine the effectiveness of Kahoot! about vocabulary mastery of class X SMAN 9 Pekanbaru. This research is an experimental research with a quasi-experimental type, where the data collection instruments used are pretest and posttest control groups. There are 2 classes with 35 students in each class. The samples in this study were class X IPA 2 as an experimental class and X IPS 2 as a control class. Based on the results of the Independent Sample T Test, then Sig. (2-tailed) of 0.000 which shows that the result is smaller than 0.05 so it can be concluded that Ha is accepted and Ho is rejected, which means that the use of Kahoot! effective in mastering vocabulary class X SMAN 9 Pekanbaru.